Answer:
<h2>x = 5/2 , x = - 4/3</h2>
Step-by-step explanation:
6x² - 7x - 20 = 0
Using method of factorization
Rewrite - 7x as a difference
That's
6x² + 8x - 15x - 20 = 0
Factor the expression
That's
2x( 3x + 4) - 5( 3x + 4) = 0
Which is
(2x - 5) (3x + 4) = 0
2x - 5 = 0
2x = 5
Divide both sides by 2
x = 5/2
3x + 4 = 0
3x = - 4
Divide both sides by 3
x = -4/3
Hope this helps you
The single factor tested in an experiment is: THE VARIABLE.
Answer:
88
Step-by-step explanation:
2+3=8
3+7=27
4+5=32
5+8=60
6+7=72
7+8=88